A Coastal Knowledge Ecology and Aesthetics of Data: Environmental Science, J. M. W. Turner, and the Bass Rock - Oliver, Susan (Romanticism on the Net)

(untitled) (Université de Montréal, 2022)
This article is concerned with the fluid boundaries that challenged artists, natural philosophers, writers, reviewers, and readers to understand Scotland and its coastal, inshore environment in radically new ways. Those boundaries are material and disciplinary, existing, on the one hand, where land meets sea and, on the other hand, where the arts and sciences interact. My enquiry explores developing forms of knowledge pertaining to the Bass Rock and its surrounding coastal waters. The Scottish marine paintings of J. M. W. Turner provide a lens for that enquiry, embodying the imaginative curiosity that characterized Romanticism while visualizing innovative understanding in the natural sciences (geology, oceanography, meteorology, botany, zoology). Interest in the Bass Rock from natural philosophers, writers, and artists during the late eighteenth and early nineteenth centuries embodied what we now regard as interdisciplinary approaches to knowledge. Examples include geologist James Hutton’s literary-scientific prose, while palaeontologist Hugh Miller vividly imagined prehistoric sea creatures swimming around the Bass. This article argues that interacting categories of understanding emerge: a “knowledge ecology” and an “aesthetics of data,” each denoting advances in forms of understanding.